Relationship of Professionalism Care with Risk of Malpractices - Rachmat Trijono (Universitas Djuanda, 2019)
Nursing care is a form of professional services is an integral part of health care that is based on nursing science and troubleshooting. Therefore, the professionalism of nurses urgently needed to avoid the risk of malpractice. Knowing and analyzing the professionalism of nurses, identify and analyze the risk of malpractice level overview of nurses, identify and analyze the influence of professionalism of nurses to the risk of malpractice. This study used a descriptive correlation with cross-sectional study design research. The sample used is purposive sampling with criteria D.III or S1 educated and have experience of at least five years, the instrument is a questionnaire with a Likert scale, α = 5%. The nurses are categorized as less professional as much as 46.7%. Professional nurses who enter the category of 53.3%, nurses who are at risk of malpractice as much as 46.67%. The relationship between the risk of occurrence of Nursing Professionalism malpractice proved insignificant. The pattern of the relationship between professionalism Nurse Occurrence Malpractice Risk shows that nurses are less professional riskier commit malpractice. While professional careers tendency is not at risk of doing malpractices. It is better to find out the relationship between professionalism and malpractice, it is necessary to conduct research with other independent variables.